Elevated suPAR Is an Independent Risk Marker for Incident Kidney Disease in Acute Medical Patients - Iversen, Esben; Houlind, Morten Baltzer; Kallemose, Thomas; Rasmussen, Line Jee Hartmann; Hornum, Mads; Feldt-Rasmussen, Bo; Hayek, Salim S.; Andersen, Ove; Eugen-Olsen, Jesper (Frontiers in Cell and Developmental Biology, 2020)
Introduction Identifying patients at high risk of developing kidney disease could lead to early clinical interventions that prevent or slow disease progression. Soluble urokinase plasminogen activator receptor (suPAR) is an inflammatory biomarker thought to be involved in the pathogenesis and development of kidney disease. We aimed to determine whether elevated plasma suPAR measured at hospital admission is associated with incident kidney disease in patients presenting to the emergency department. Materials and Methods This was a retrospective registry-based cohort study performed at the Emergency Department of Copenhagen University Hospital Amager and Hvidovre, Hvidovre, Denmark. Acute medical patients were included in the study from November 2013 to March 2017 and followed until June 2017. Patients were excluded if they were diagnosed with kidney disease or died prior to index discharge. Plasma suPAR was measured at hospital admission, and the main outcome was time to incident kidney disease, defined by ICD-10 diagnosis codes for both chronic and acute kidney conditions. Association between suPAR and time to incident kidney disease was assessed by Cox proportional hazard regression analysis. Results In total, 25,497 acute medical patients (median age 58.1 years; 52.5% female) were followed for development of kidney disease. During a median follow-up time of 2 years, 760 patients (3.0%) developed kidney disease. In multivariable Cox regression analysis adjusting for age, sex, eGFR, CRP, cardiovascular disease, hypertension, and diabetes, each doubling in suPAR at hospital admission was associated with a hazard ratio of 1.57 (95% CI: 1.38–1.78, P<0.001) for developing a chronic kidney condition and 2.51 (95% CI: 2.09–3.01, P<0.001) for developing an acute kidney condition. Discussion In a large cohort of acutely hospitalized medical patients, elevated suPAR was independently associated with incident chronic and acute kidney conditions. This highlights the potential for using suPAR in risk classification models to identify high-risk patients who could benefit from early clinical interventions. The main limitation of this study is its reliance on accurate reporting of ICD-10 codes for kidney disease.